The Economics of Super Managers - Baranchuk, Nina; MacDonald, Glenn; Yang, Jun (Review of Financial Studies, 2011)
We study a competitive model in which managers differ in ability and choose unobservable effort. Each firm chooses its size, how able a manager is to hire, and managerial compensation. The model can be considered an amalgam of agency and Superstars, where optimizing incentives enhances the firm's ability to provide a talented manager with greater resources. The model delivers many testable implications. Preliminary results show that the model is useful for understanding interesting compensation trends, for example, why CEO pay has recently become more closely associated with firm size. Allowing for firm productivity differences generally strengthens our results.